Ethnomathematical Exploration of Two-Dimensional Shapes in Banten Batik Motifs - Nirmalasari, Dinar; Rofiroh, Rofiroh (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2025)
Indonesia is currently implementing an independent curriculum that emphasizes contextual, differentiated, and learner-centered instruction grounded in students’ cultural environments. Integrating local heritage, such as batik, aligns with these principles and allows students to recognize mathematics as part of their everyday experiences rather than a detached school subject. Typical Banten batik, therefore, holds strong potential as a medium for teaching geometry. This study aims to identify and analyze the plane shapes embedded in Banten batik motifs. A descriptive qualitative method with an ethnographic approach was employed. Data were collected through literature review, interviews, and direct observations of Banten batik, and were analyzed using domain and taxonomic techniques to classify and interpret geometric features. The findings show that Banten batik motifs contain plane geometric elements that represent mathematical concepts naturally embedded in local culture, demonstrating clear connections with flat shapes. The study highlights the significant potential of ethnomathematics-based learning, enabling teachers to connect formal mathematics with students’ cultural knowledge, promote meaningful learning, and strengthen students’ cultural identity and pride.